General Name as Cultural Code of Siberian Tatars - Rifkatovich Zamaletdinov, Radif; Chakhvarovna Fajzullina, Guzel (International Journal of Criminology and Sociology, 2022)
The article actualizes the problems of studying the pedigree and generic names of the Siberian Tatars in the linguocultural aspect. The source of the research is the Russian-language documents of the regional archive of the XVIII-XIX centuries, which recorded information on the composition of the family of residents of the Otdelno-Babasan volost of the Tobolsk province. Today, the issue of updating and preserving the language and culture of the Siberian Tatars is extremely acute, since the dialects of the natives of Western Siberia, according to UNESCO, are at the stage of extinction. The work has an integrated approach, therefore the following methods are used: the method of linguoculturological analysis, the method of interviewing informants, the method of language coexistence, the genealogical method, the descriptive-analytical method, the method of comparing definitions, the method of etymological analysis, the method of lexicographic description, the quantitative-statistical method The classification of generic names by etymology and structure is made, the models of the name of the deceased relative are identified, the traditions of the name of the deceased by the name of the deceased relative in Turkic cultures are examined, the mechanisms of metaphorization of kinship terms are determined. The authors come to the conclusion that the patrimonial names of the Siberian Tatars are a cultural code that stores echoes of the archaic world, namely the cult of their ancestors.